Frederick Street, Looking South, Trinidad - (:unkn) unknown (My University, 2010)
A view of tree lined Frederick Street. In the distance a tram car can be seen.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago; Streets--Trinidad and Tobago; Street-railroads--Trinidad and Tobago; Buildings--Trinidad and Tobago; Trees--Trinidad and Tobago